2020
DOI: 10.1038/s41467-020-19906-3
|View full text |Cite
|
Sign up to set email alerts
|

Foreign body responses in mouse central nervous system mimic natural wound responses and alter biomaterial functions

Abstract: Biomaterials hold promise for therapeutic applications in the central nervous system (CNS). Little is known about molecular factors that determine CNS foreign body responses (FBRs) in vivo, or about how such responses influence biomaterial function. Here, we probed these factors in mice using a platform of injectable hydrogels readily modified to present interfaces with different physiochemical properties to host cells. We found that biomaterial FBRs mimic specialized multicellular CNS wound responses not pres… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
82
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 45 publications
(94 citation statements)
references
References 73 publications
(123 reference statements)
3
82
0
Order By: Relevance
“…While scaffold implantation may clear some of the physical barriers to axon growth, astrogliosis can rapidly encapsulate the implanted biomaterial. [ 13 ] Indeed, implant materials that provoke a foreign body inflammatory response can worsen the surrounding glial scar and even exacerbate axonal degeneration, resulting in further loss of function. For example, collagen type‐I (a commonly used biomaterial) stimulates astrocyte reactivity—resulting in denser scarring and inhibiting repair.…”
Section: Introductionmentioning
confidence: 99%
“…While scaffold implantation may clear some of the physical barriers to axon growth, astrogliosis can rapidly encapsulate the implanted biomaterial. [ 13 ] Indeed, implant materials that provoke a foreign body inflammatory response can worsen the surrounding glial scar and even exacerbate axonal degeneration, resulting in further loss of function. For example, collagen type‐I (a commonly used biomaterial) stimulates astrocyte reactivity—resulting in denser scarring and inhibiting repair.…”
Section: Introductionmentioning
confidence: 99%
“…[389][390][391][392][393] Recently, it has been demonstrated that cationic biomaterials, when implanted in rodent brains, lead to a foreign body response that is detrimental to brain parenchyma. [394] Cationic interfaces resulted in stromal cell infiltration, peripherally derived inflammation, neural damage and amyloid production. In contrast, they noted that nonionic and anionic formulations of hydrogels resulted in minimal levels of these responses resulting in better resorption and molecular delivery.…”
Section: Therapies and Engineering Solutions To Disease Stemmed From Neuromechanobiologymentioning
confidence: 99%
“…For example, Th1 CD4 + T cells are more prone to promote proinflammatory M1 macrophage activation, Th2 CD4 + T cells are more prone to promote more anti-inflammatory M2 macrophages, and Th17 CD4 + T cells can induce recruitment and activation of neutrophils [ 46 ]. Biomaterials implanted in the CNS may cause a chronic inflammation with fibrotic lesion formation similar to a scar after a CNS injury to restrict the injury site [ 47 ]. Physical properties of the biomaterials, like shape, surface features and electrical charge, have been shown to affect the immunological response, as described by Andorko et al and O’Shea et al [ 46 , 47 ].…”
Section: Introductionmentioning
confidence: 99%
“…Biomaterials implanted in the CNS may cause a chronic inflammation with fibrotic lesion formation similar to a scar after a CNS injury to restrict the injury site [ 47 ]. Physical properties of the biomaterials, like shape, surface features and electrical charge, have been shown to affect the immunological response, as described by Andorko et al and O’Shea et al [ 46 , 47 ]. In regenerative medicine, a certain degree of a controlled immune response may even be desired to slowly degrade an implanted biomaterial scaffold while supporting the transplanted cells to survive and proliferate until full integration into the host tissue is achieved.…”
Section: Introductionmentioning
confidence: 99%